Method for producing high strength ceramic particles and method for producing microporous spherical particles for aerosol generators using Benard cellular phenomenon
By mixing metal ion-bound silicate powder with low-temperature firing glass powder and adding polymer and dispersant to prepare high-strength ceramic particles, the problems of local carbonization of the liquid phase and insufficient specific surface area in the aerosol generator are solved, and efficient liquid phase absorption and aerosol generation are achieved.
Patent Information
- Application Number
- CN202380045063.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-01-31
- Publication Date
- 2025-02-28
AI Technical Summary
The vaporization unit of the existing aerosol generator may lead to local carbonization of the liquid phase due to the difference in heat transfer rate between the core and the coil, and the specific surface area of the porous ceramic is not sufficient to increase the atomization amount.
A mixture of silicate powder particles combined with metal ions and glass powder particles for low-temperature firing is used to prepare high-strength ceramic particles by adding polymers and dispersant, and microporous spherical particles are prepared in an aerosol generator using the Bernard cell effect to increase their specific surface area.
The specific surface area and strength of ceramic particles are improved, the absorption of liquid phase and the production of aerosol are enhanced, and the problems of local carbonization of liquid phase and insufficient specific surface area are solved.
Smart Images

Figure CN119546385A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to methods for preparing high-strength ceramic particles. Background Art
[0002] Figure 1 is a top perspective view of a vaporization unit of an aerosol generator according to the related art, and Figure 2 is a bottom perspective view of a vaporization unit of an aerosol generator according to the related art.
[0003] When an aerosol generator uses a wick and coil assembly as a vaporization unit, there is a possibility that the liquid phase and the wick will be partially carbonized due to the difference in heat transfer rate between the wick and the coil. To solve this problem, a Figure 1 and Figure 2 The vaporization unit of the aerosol generator shown in the figure, and the vaporization unit of the fine particle generator according to the first embodiment of the present disclosure includes a porous ceramic 10 that absorbs and supports a liquid phase and a heating element 16 attached to the lower surface of the porous ceramic 10 to heat and vaporize the liquid phase. A power line 14 for applying current to the heating element 16 can be connected to the heating element 16 attached to the surface of the porous ceramic 10.
[0004] The porous ceramic 10 includes the recess 12 serving as a reservoir in which a liquid phase can be contained at its center. By providing a reservoir in which a liquid phase can be contained, the liquid phase can be continuously supplied to the pores of the porous ceramic 10 more stably.
[0005] Furthermore, in the porous ceramic 10 , at high temperatures, the movement of the liquid phase is slow and the movement of the aerosol is smooth, and the pores of the porous ceramic 10 may be connected to form channels through which the aerosol may pass.
[0006] Here, as the specific surface area of the porous ceramic 10 increases, the absorption amount of the liquid phase may increase, thereby increasing the amount of atomization.
[0007] Therefore, in order to use the porous ceramic 10 as a vaporization unit for an aerosol generator, it is necessary to develop a preparation method capable of increasing the specific surface area of the porous ceramic 10 . Summary of the invention
[0008] One aspect of the present disclosure provides a method for preparing high-strength ceramic particles.
[0009] Another aspect of the present disclosure provides a method for preparing microporous spherical particles for an aerosol generator using the Benard cell effect.
[0010] One embodiment provides a method for preparing high-strength ceramic particles, the preparation method comprising: a first step of mixing silicate powder particles combined with metal ions with glass powder particles for low-temperature firing; a second step of adding a polymer and a dispersant to the mixed powder particles and preparing ceramic granules; a third step of pressing the ceramic granules into shape; and a fourth step of sintering the formed body.
[0011] Another aspect of one embodiment provides a method for preparing high-strength ceramic particles, wherein the silicate powder particles may contain one or more metal ions selected from Mg, Al, Zr, Li, Ba, MgAl, Na and Ca.
[0012] Another aspect of one embodiment provides a method for preparing high-strength ceramic particles, wherein the specific surface area of the silicate powder particles combined with metal ions measured by the Brunauer-Emmett-Teller (BET) method can be 20 m 2 / g to 500m 2 / g.
[0013] Another aspect of an embodiment provides a method for preparing high-strength ceramic particles, wherein the average particle size of the silicate powder particles combined with metal ions may be 5 μm to 500 μm.
[0014] Another aspect of one embodiment provides a method for preparing high-strength ceramic particles, wherein the glass powder particles for low-temperature firing may be one or more selected from ceramic powder particles for low-temperature firing and amorphous glass powder particles.
[0015] Another aspect of one embodiment provides a method for preparing high-strength ceramic particles, wherein the glass powder particles for low-temperature firing may have any one of a plate shape, a fiber shape, and a polygonal shape.
[0016] Another aspect of an embodiment provides a method for preparing high-strength ceramic particles, wherein a suitable firing temperature range of the low-temperature firing glass powder particles may be 600°C to 1200°C.
[0017] Another aspect of an embodiment provides a method for preparing high-strength ceramic particles, wherein the average particle size of the glass powder particles for low-temperature firing may be 0.5 μm to 50 μm.
[0018] Another aspect of one embodiment provides a method for preparing high-strength ceramic particles, wherein glass powder particles for low-temperature firing may be mixed at 1 to 500 parts by weight relative to silicate powder particles combined with metal ions.
[0019] Another aspect of an embodiment provides a method for preparing high-strength ceramic particles, wherein the polymer added in the second step can be one or more selected from the following: polyvinyl alcohol, polyvinyl acetate, polyethylene, polyvinyl butene, polypropylene, polyvinyl chloride, polyacrylamide, polyacrylamide, guar gum, gelatin and natural rubber.
[0020] Another aspect of an embodiment provides a method for preparing high-strength ceramic particles, wherein the dispersant added in the second step may be a wettable dispersant.
[0021] Another aspect of an embodiment provides a method for preparing high-strength ceramic particles, wherein the ceramic granules prepared in the second step may have an average particle size of 50 μm to 1000 μm.
[0022] Another aspect of an embodiment provides a method for preparing high-strength ceramic particles, wherein the sintering in the fourth step may be performed at a temperature ranging from 600°C to 1200°C.
[0023] Another aspect of an embodiment provides a method for preparing high-strength ceramic particles, wherein, during the sintering process of the fourth step, a ceramic core-shell structure can be formed by surface melting and necking of low-temperature fired glass powder particles.
[0024] Another aspect of one embodiment provides a method for preparing high-strength ceramic particles, wherein the high-strength ceramic particles subjected to a sintering process in the fourth step may have a porous structure.
[0025] Another embodiment provides a method for preparing microporous spherical particles for an aerosol generator, the preparation method comprising: preparing a first dispersion solution by dispersing silicate powder particles bound with metal ions and a binder in a first solvent; preparing a second dispersion solution by dispersing an additive in a second solvent and stirring the second solvent in which the additive is dispersed; mixing the first dispersion solution with the second dispersion solution and stirring the mixture to prepare a mixed slurry; and spray drying the mixed slurry.
[0026] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein the metal silicate powder particles may contain one or more metal ions selected from Mg, Al, Zr, Li, Ba, MgAl, Na and Ca.
[0027] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein the metal silicate powder particles may be dispersed in an amount of 5 wt % to 40 wt % relative to the first solvent.
[0028] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein the binder used in preparing the first dispersion solution can be one or more selected from the following: polyvinyl alcohol, polyvinyl acetate, polyethylene, polyvinyl butene, polypropylene, polyvinyl chloride, polyacrylamide, polyacrylamide, guar gum, gelatin and natural rubber.
[0029] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein the first solvent may include at least one selected from the group consisting of water, ethanol, toluene, IPA, and acetone.
[0030] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein the first solvent may be used in an amount of 70 wt % to 220 wt % relative to the weight of the metal silicate.
[0031] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein the additive used in preparing the first dispersion solution may include a high boiling point solvent, and the high boiling point solvent includes mineral spirits or xylene.
[0032] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein the additive may be added in an amount of 0.5 wt % to 10 wt % relative to the metal silicate.
[0033] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein the second solution may include one or more selected from the group consisting of water, ethanol, toluene, IPA, and acetone.
[0034] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein the second solvent used in preparing the second dispersion solution may be included in an amount of 5 wt % to 30 wt % relative to the metal silicate.
[0035] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein the spray drying uses a disk method, and the rotation speed of the disk can be controlled within a range of 500 rpm to 9000 rpm.
[0036] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein spray drying can be carried out in a chamber maintained at a temperature of 220°C to 300°C, and during the spray drying step, the Bénard cell effect can be induced to produce defects on the surface of the microporous spherical particles.
[0037] Another aspect of an embodiment provides a method for preparing microporous spherical particles for an aerosol generator, wherein the average particle size of the microporous spherical particles finally prepared after spray drying may be 5 μm to 500 μm.
[0038] Beneficial Effects
[0039] The ceramic getter material prepared by the method for preparing a high-strength ceramic getter material provided by the embodiment has a core-shell structure, thereby advantageously having high strength.
[0040] In addition, the advantage of the ceramic heater for an aerosol generator prepared by the method for preparing microporous spherical particles for an aerosol generator using the Bénard cell effect provided in the embodiment is that defects can be induced on the surface of the particles through the Bénard cell effect, causing the specific surface area of the porous spherical particles to increase, and thus, the absorption amount of the liquid phase can be increased, and ultimately the amount of aerosol generated can be increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a top perspective view of a vaporization unit of an aerosol generator according to the related art.
[0042] Figure 2 is a bottom perspective view of a vaporization unit of an aerosol generator according to the related art.
[0043] Figure 3 FIG. 4 is a top view of a vaporization unit of an aerosol generator according to the related art.
[0044] Figure 4 is a flow chart of a method for preparing high-strength ceramic particles according to the first embodiment.
[0045] Figure 5 Schematic diagram of a ceramic core-shell structure prepared according to the method for preparing high-strength ceramic particles according to the first embodiment.
[0046] Figure 6 : is a scanning microscope photograph of a ceramic core-shell structure prepared according to the method for preparing high-strength ceramic particles according to the first embodiment.
[0047] Figure 7 It is a flow chart of a method for preparing microporous spherical particles for an aerosol generator using the Bernard cell effect according to the second embodiment.
[0048] Figure 8 It is a scanning micrograph of microporous spherical particles prepared according to the method for preparing microporous spherical particles for an aerosol generator using the Bernard cell effect according to the second embodiment. DETAILED DESCRIPTION
[0049] Hereinafter, the present disclosure will be described in detail with reference to the accompanying drawings.
[0050] Figure 4 is a flow chart of a method for preparing high-strength ceramic particles according to a first embodiment, Figure 5 is a schematic diagram of a ceramic core-shell structure prepared according to the method for preparing high-strength ceramic particles according to the first embodiment, and Figure 6 : is a scanning microscope photograph of a ceramic core-shell structure prepared according to the method for preparing high-strength ceramic particles according to the first embodiment.
[0051] According to one embodiment, a method for preparing high-strength ceramic particles includes: a first step (S1) of mixing silicate powder particles combined with metal ions with glass powder particles for low-temperature firing, a second step (S2) of adding a polymer and a dispersant to the mixed powder particles and preparing ceramic granules, a third step (S3) of pressing the ceramic granules, and a fourth step (S4) of sintering the green body.
[0052] Here, the silicate powder particles mixed in the first step contain one or more metal ions selected from Mg, Al, Zr, Li, Ba, MgAl, Na and Ca. Here, the specific surface area of the silicate powder particles bound with the metal ions measured by the Brunauer-Emmett-Teller (BET) method is preferably 100 m 2 / g to 450m 2 / g, and the average particle size of the metal ion-bound silicate powder particles is preferably 5 to 500 μm. If the average particle size of the metal ion-bound silicate powder particles exceeds 500 μm, it may be difficult to form spherical beads using a spray drying method.
[0053] In addition, the low-temperature firing glass powder particles mixed with the silicate powder particles in the first step are preferably at least one selected from amorphous glass powder particles and low-temperature firing ceramic powder particles. Here, the low-temperature firing ceramic powder particles include Bi2O3, Sb2O5, B2O3, etc.
[0054] Here, the glass powder particles for low temperature firing may have any one of a sheet shape, a fiber shape, and a polygonal shape, and the glass powder particles for low temperature firing preferably have a suitable firing temperature range of 600°C to 1200°C. In addition, the average particle size of the glass powder particles for low temperature firing is preferably 0.5 μm to 50 μm. The glass powder particles are added as a liquid phase sintering agent that promotes firing, and if the average particle size of the glass powder particles for low temperature firing is greater than 50 μm, the distance between the silicate powder particles may increase, thereby reducing the firing effect under the same temperature distribution. Therefore, the average particle size of the glass powder particles for low temperature firing is 50 microns or less.
[0055] Here, the glass powder particles for low-temperature firing are mixed in an amount of 1 to 500 parts by weight relative to the silicate powder particles combined with metal ions. In this case, when 1 to 80 parts by weight of the glass powder particles for low-temperature firing are mixed with the silicate powder particles combined with metal ions, the silicate powder particles combined with metal ions have a larger volume portion and have strong hydrophilicity. At the same time, when 80 to 500 parts by weight of the glass powder particles for low-temperature firing are mixed with the silicate powder particles combined with metal ions, the volume occupied by the glass powder particles for low-temperature firing is greater than the volume occupied by the silicate powder particles, and the hydrophobicity is stronger.
[0056] Hydrophobicity or hydrophilicity can be achieved by adjusting the mixing ratio of the low-temperature fired glass powder particles according to the purpose of the high-strength ceramic particles. The high-strength ceramic particles thus prepared can be used as they are in the form of beads, or the beads can be mixed with a binder to form a block used as a heater or liquid phase storage unit of an aerosol generator.
[0057] [Table 1]
[0058]
[0059] Table 1 summarizes the measured values of the bending strength according to the amount of the added glass powder particles for low temperature firing. It can be seen that the bending strength increases with the increase in the amount of the added glass powder particles for low temperature firing. Meanwhile, the polymer added in the second step is one or more materials selected from polyvinyl alcohol, polyvinyl acetate, polyethylene, polyvinyl butene, polypropylene, polyvinyl chloride, polyacrylamide, polyacrylamide, guar gum, gelatin and natural rubber, and the dispersant is preferably a wettable dispersant.
[0060] The average particle size of the ceramic granules prepared in the second step is preferably 50 μm to 1000 μm.
[0061] Meanwhile, in the third step, ceramic granules are formed by uniaxial or multiaxial pressing, and the ceramic getter material is compression-molded to have a desired shape.
[0062] The sintering in the fourth step is preferably performed in a temperature range of 600°C to 1200°C according to the appropriate firing temperature of the glass powder particles for low-temperature firing.
[0063] Through the sintering process of the fourth step, a ceramic core-shell structure is formed by surface melting and necking of the low-temperature firing glass powder particles. That is, by adding low-temperature firing glass powder particles to the silicate powder particles combined with metal ions that need to be fired at a high temperature of 1600° C. or higher, the high-strength ceramic particles advantageously have a fracture strength of 1 MPa or more even when sintered at a relatively low temperature of 600° C. to 1200° C.
[0064] At the same time, the high-strength ceramic particles prepared according to the method of the embodiment can be installed in an aerosol generator and used for liquid absorption or for a carrier. In addition, the high-strength ceramic particles can be applied to any situation where an absorbent material that needs to accommodate liquid while maintaining high strength is required.
[0065] Figure 7 is a flow chart of a method for preparing microporous spherical particles for an aerosol generator using the Bernard cell effect according to the second embodiment, and Figure 8 It is a scanning micrograph of microporous spherical particles prepared according to the method for preparing microporous spherical particles for an aerosol generator using the Bernard cell effect according to the second embodiment.
[0066] According to one embodiment, a method for preparing microporous spherical particles for an aerosol generator utilizing the Bénard cell effect includes: a step of preparing a first dispersion solution by dispersing silicate powder particles bound with metal ions and a binder in a first solvent, a step of preparing a second dispersion solution by dispersing an additive in a second solvent and stirring the same, a step of preparing a mixed slurry by mixing the first dispersion solution and the second dispersion solution and stirring the mixed solution, and a step of spray-drying the mixed slurry.
[0067] Here, the metal silicate powder particles preferably contain one or more metal ions selected from Mg, Al, Zr, Li, Ba, MgAl, Na and Ca, and are dispersed in an amount of 5 wt % to 40 wt % relative to the first solvent.
[0068] Meanwhile, the binder used in preparing the first dispersion solution is preferably one or more selected from the group consisting of polyvinyl alcohol, polyvinyl acetate, polyethylene, polyvinyl butene, polypropylene, polyvinyl chloride, polyacrylamide, polyacrylamide, guar gum, gelatin and natural rubber.
[0069] Furthermore, the first solvent includes one or more selected from water, ethanol, toluene, IPA, and acetone, and is preferably used in an amount of 70 wt % to 220 wt % relative to the weight of the metal silicate.
[0070] Here, the additive used in preparing the first dispersion solution preferably includes a high boiling point solvent such as solvent oil or xylene, and is preferably added in an amount of 0.5 wt % to 10 wt % relative to the metal silicate. This depends on the additive, but in the case of an organic additive, when the organic additive is added in an amount of 10 wt % or more, the bead shape may not be maintained, high viscosity may be caused, and processability may be deteriorated.
[0071] Furthermore, the second solution includes one or more selected from water, ethanol, toluene, IPA, and acetone, and is preferably added in an amount of 5 wt % to 30 wt % relative to the metal silicate.
[0072] The first dispersion solution and the second dispersion solution are mixed and stirred to prepare a mixed slurry, and then the mixed slurry is spray dried to form microporous spherical particles. Here, the spray drying uses a disc method, and the rotation speed of the disc is preferably adjusted in the range of 500rpm to 9000rpm. If the rotation speed of the disc is less than 500rpm, the effect based on centrifugal force is not significant, and the spherical particles become too large. At the same time, if the rotation speed of the rotating disc exceeds 9000rpm, the rate of generating spherical particles of 20μm or less may increase, and when preparing a heater or liquid phase absorbent material of an aerosol generator, these small spherical particles may block the surface pores of the heater or liquid phase absorbent material, thereby reducing the specific surface area. Therefore, it is preferred that the rotation speed of the disc is adjusted in the range of 500rpm to 9000rpm.
[0073] The disk from which the mixed slurry is sprayed is rotated in a chamber maintained at a temperature of 220° C. to 300° C., and the Bénard cell effect can be induced in the spray drying step, causing Figure 8 The surface defects (cracks) shown in the photo of the microporous spherical particles are removed, thereby increasing the specific surface area of the microporous spherical particles. In this case, the microporous spherical particles can advantageously form micropores without adding a pore-forming agent separately during the preparation process. The microporous spherical particles thus prepared can increase the specific surface area. Therefore, when a heater or a liquid phase absorbent material of an aerosol generator is prepared using microporous spherical particles for an aerosol generator using the Bernard cell effect according to one embodiment, the amount of moisture absorption that can absorb the liquid phase can be increased, and therefore, the amount of atomization that can be generated by vaporizing the liquid phase can be increased.
Claims
1. A method for preparing high-strength ceramic particles, the preparation method comprising: A first step of mixing silicate powder particles bonded with metal ions with glass powder particles for low temperature firing; A second step of adding a polymer and a dispersant to the mixed powder particles and preparing a ceramic granulate; a third step of pressing and molding the ceramic granules; and The fourth step is to sinter the molded body.
2. The preparation method according to claim 1, wherein the silicate powder particles contain one or more metal ions selected from Mg, Al, Zr, Li, Ba, MgAl, Na and Ca.
3. The preparation method according to claim 2, wherein the specific surface area of the silicate powder particles bound with metal ions measured by the Brunauer-Emmett-Teller (BET) method is 20 m 2 / g to 500m 2 / g. 4 . The preparation method according to claim 2 , wherein the average particle size of the silicate powder particles combined with metal ions is 5 μm to 500 μm. 5 . The preparation method according to claim 1 , wherein the glass powder particles for low-temperature firing are one or more selected from ceramic powder particles for low-temperature firing and amorphous glass powder particles. 6 . The production method according to claim 5 , wherein the glass powder particles for low-temperature firing have any one of a flake shape, a fiber shape, and a polygonal shape.
7. The preparation method according to claim 5, wherein a suitable firing temperature range of the low-temperature firing glass powder particles is 600°C to 1200°C. 8 . The preparation method according to claim 5 , wherein the average particle size of the glass powder particles for low-temperature firing is 0.5 μm to 50 μm. 9 . The preparation method according to claim 1 , wherein the glass powder particles for low-temperature firing are mixed in an amount of 1 part by weight to 500 parts by weight relative to the silicate powder particles to which metal ions are bonded.
10. The preparation method according to claim 1, wherein the polymer added in the second step is one or more selected from the group consisting of polyvinyl alcohol, polyvinyl acetate, polyethylene, polyvinyl butene, polypropylene, polyvinyl chloride, polyacrylamide, polyacrylamide, guar gum, gelatin and natural rubber.
11. The preparation method according to claim 1, wherein the dispersant added in the second step is a wettable dispersant. 12 . The preparation method according to claim 1 , wherein the ceramic granules prepared in the second step have an average particle size of 50 μm to 1000 μm.
13. The preparation method according to claim 1, wherein the sintering in the fourth step is performed at a temperature ranging from 600°C to 1200°C.
14. The preparation method according to claim 1, wherein: During the sintering process of the fourth step, a ceramic core-shell structure is formed by surface melting and necking of the low-temperature firing glass powder particles.
15. The preparation method according to claim 1, wherein the high-strength ceramic particles subjected to the sintering process in the fourth step have a porous structure.
16. A method for preparing microporous spherical particles for an aerosol generator, the method comprising: preparing a first dispersion solution by dispersing silicate powder particles bound with metal ions and a binder in a first solvent; preparing a second dispersion solution by dispersing an additive in a second solvent and stirring the second solvent in which the additive is dispersed; mixing the first dispersion solution and the second dispersion solution, and stirring the mixture to prepare a mixed slurry; as well as The mixed slurry is spray dried.
17. The preparation method according to claim 16, wherein the metal silicate powder particles contain one or more metal ions selected from Mg, Al, Zr, Li, Ba, MgAl, Na and Ca. 18 . The preparation method according to claim 16 , wherein the metal silicate powder particles are dispersed in an amount of 5 wt % to 40 wt % relative to the first solvent.
19. The preparation method according to claim 16, wherein the binder used in preparing the first dispersion solution is one or more selected from the group consisting of polyvinyl alcohol, polyvinyl acetate, polyethylene, polyvinyl butene, polypropylene, polyvinyl chloride, polyacrylamide, polyacrylamide, guar gum, gelatin and natural rubber.
20. The preparation method according to claim 16, wherein the first solvent comprises at least one selected from the group consisting of water, ethanol, toluene, IPA, and acetone. 21 . The preparation method according to claim 20 , wherein the first solvent is used in an amount of 70 wt % to 220 wt % relative to the weight of the metal silicate. 22 . The preparation method according to claim 16 , wherein the additive used in preparing the first dispersion solution comprises a high boiling point solvent, and the high boiling point solvent comprises mineral spirits or xylene.
23. The preparation method according to claim 22, wherein the additive is added in an amount of 0.5 wt% to 10 wt% relative to the metal silicate.
24. The preparation method according to claim 16, wherein the second solution comprises one or more selected from water, ethanol, toluene, IPA and acetone. 25 . The preparation method according to claim 24 , wherein the second solvent used in preparing the second dispersion solution is included in an amount of 5 wt % to 30 wt % relative to the metal silicate. 26 . The preparation method according to claim 16 , wherein the spray drying uses a disk method, and the rotation speed of the disk is controlled within a range of 500 rpm to 9000 rpm.
27. The preparation method according to claim 16, wherein the spray drying is performed in a chamber maintained at a temperature of 220°C to 300°C, and in the spray drying step, a Bénard cell effect is induced to generate defects on the surface of the microporous spherical particles. 28 . The preparation method according to claim 16 , wherein the average particle size of the microporous spherical particles finally prepared after the spray drying is 5 μm to 500 μm.